TEMPERATURE AND MAGNETIC FIELD DEPENDENCES OF THERMOELECTRIC POWER IN ELECTRONIC ANTIMONIDE INDIUM - M. M. Gadjialiev; Z. Sh. Pirmagomedov; T. N. Efendieva (Вестник Дагестанского государственного технического университета: Технические науки)
We have researched the thermoelectric power of electronic antimonide indium with n=21014 cm-3 in a transverse magnetic field up to 7 kOe in temperature intervals from 4.8 K to 120 K. The thermoelectric power is found to be independent from the energy field at the temperature close to 56 K.